If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -7(313x) + -9 = 0 Remove parenthesis around (313x) 4x + -7 * 313x + -9 = 0 Multiply -7 * 313 4x + -2191x + -9 = 0 Reorder the terms: -9 + 4x + -2191x = 0 Combine like terms: 4x + -2191x = -2187x -9 + -2187x = 0 Solving -9 + -2187x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2187x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2187x = 0 + 9 -2187x = 0 + 9 Combine like terms: 0 + 9 = 9 -2187x = 9 Divide each side by '-2187'. x = -0.004115226337 Simplifying x = -0.004115226337
| 3(k-2)-7=3k-(2k-1) | | -x-144=38-9x | | 0.72x-11=2.32x+21 | | -5(r-5)+7(r-1)=-78 | | 4x+20=-10 | | 7-23+15-36= | | 9.1=1.4-6.3 | | 7m+6-8m=36 | | 12v^2+23v-24=0 | | 2-x=-22 | | (2x+6)+(2x+5)+(2x)=(2x)+(2x)+(3x+6) | | n-mn=4k+3 | | 6x+7x-76=38-6x | | 0=12x-3y | | -38=5(x-7)-8x | | 15y^3-25y^2=0 | | 8=3+6 | | 7x-192=-3x+56 | | 2+y^3=-1 | | 5(1-7a)+6(1-2a)=11 | | 6y+9=3(2-d) | | -6(3x-2)=5 | | x-46=-63 | | 5y+3y-2y=48 | | 25=9x+5-5x | | 3(5x-3)-6x=3(3x+2) | | 72+40=36+x | | 21+25m=28+18m | | 3y-6=2x+4 | | 13-17+24= | | 36-(2x+4)=2(x+6)+x | | 10-2(y-7)=3y+9 |